Practical theology: A current international perspective - Osmer, Richard R. (HTS teologiese studies, 2011)
Drawing on Thomas Kuhn’s concept of paradigms, this article explored two levels at which paradigms influence contemporary practical theology. The first level is reflective practice, where pastors and academics carry out the descriptive-empirical, interpretive, normative and pragmatic tasks of practical theological reflection on particular contexts. The second level is metatheoretical, where practical theologians make decisions about how they view the theory– praxis relationship, interdisciplinary work, the relative weight of Scripture, tradition, reason, and experience and the theological rationale that justifies their approach. The article concluded by raising two challenges to the current paradigms of practical theology: the relationship between Christian particularity and the common good, and the wound of reason.